How common is repeat surgery and multi-level treatment in Degenerative Cervical Myelopathy? Findings from a patient perspective survey. (July 2020) - Gharooni, Aref-Ali; Grodzinski, Ben; Davies, Benjamin M.; Kotter, Mark R.N.
Highlights: Multi-Level DCM is common, and patient characteristics are similar to single level. Recurrent DCM is more prevalent in internet population than conventional studies. Recurrent disease behaves in similar manner to primary disease. Exclusion of recurrent disease subgroups from trials is not always necessary. Abstract: Degenerative Cervical Myelopathy (DCM) is a common condition which causes significant disability and reduces health-related quality of life. The only evidence-based treatment and current management guidance is surgery to decompress the spinal cord and stop further damage in moderate to severe cases. However, this guidance is mainly informed by studies that only include first time surgery and/or single level disease, but DCM can reoccur after primary surgery and affect multiple levels of the spine. It is unclear whether patients in these subgroups; repeat surgery and multi-level DCM, differ significantly in their baseline and disease characteristics from those with single-level, single-operation disease. To investigate this, we conducted an online survey of people with DCM looking at key demographic, disease (e.g. mJOA) and treatment characteristics. We received a total of 778 respondents, of which 159 (20%) had undergone surgery for DCM. Around 75% of these respondents had a single operation and 65% at a single level. We found no statistically significant difference in key participant and disease characteristics between respondents with single-level or single-operation and those with multi-level DCM or multiple operations. These data support generalisability of research to these subgroups but also warrants further investigations as these subgroups are underrepresented in current research.